2010
DOI: 10.1186/1476-511x-9-57
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive actions of eicosapentaenoic acid on lipid droplet formation in 3T3-L1 adipocytes

Abstract: BackgroundLipid droplet (LD) formation and size regulation reflects both lipid influx and efflux, and is central in the regulation of adipocyte metabolism, including adipokine secretion. The length and degree of dietary fatty acid (FA) unsaturation is implicated in LD formation and regulation in adipocytes. The aims of this study were to establish the impact of eicosapentaenoic acid (EPA; C20:5n-3) in comparison to SFA (STA; stearic acid, C18:0) and MUFA (OLA; oleic acid, C18:1n-9) on 3T3-L1 adipocyte LD forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 51 publications
8
51
2
7
Order By: Relevance
“…It has been reported that EPA and DHA inhibit SREBP-1c gene transcription, enhance SREBP-1c mRNA turnover and interfere with the proteolysis processing of SREBP-1c protein (11,12). Furthermore, in another key tissue concerned with whole body lipid metabolism, it has been shown using the in vitro cell model 3T3-L1 adipocytes that EPA suppresses lipid droplet formation by suppression of the expression levels of genes related with lipid droplet function such as Cidea and Stearoyl-CoA Desaturases (13). To date, there is no data available on the effect of DPA on gene or protein expression levels of the main upstream controller of lipogenic genes, SREBP-1c.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that EPA and DHA inhibit SREBP-1c gene transcription, enhance SREBP-1c mRNA turnover and interfere with the proteolysis processing of SREBP-1c protein (11,12). Furthermore, in another key tissue concerned with whole body lipid metabolism, it has been shown using the in vitro cell model 3T3-L1 adipocytes that EPA suppresses lipid droplet formation by suppression of the expression levels of genes related with lipid droplet function such as Cidea and Stearoyl-CoA Desaturases (13). To date, there is no data available on the effect of DPA on gene or protein expression levels of the main upstream controller of lipogenic genes, SREBP-1c.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de la diabetes tipo 2 y el síndrome metabólico, en animales de laboratorio se ha mostrado que la suplementación con DHA y EPA mejora parámetros metabólicos como la glucosa, insulina, colesterol, lipoproteínas de baja densidad y triglicéridos en sangre (17,18). Además presentan una disminución en el tamaño de los adipocitos, y el aumento en la expresión de genes de vías como la lipolisis (degradación de los ácidos grasos) y β-oxidación (conversión de los ácidos grasos en energía) en este mismo tejido (19,20).…”
Section: Omegaunclassified
“…En estudios sobre esteatosis hepática, se descubrió que el EPA disminuye la esteatosis de manera independiente a su interacción con el PPAR-α, esto se traduce en una menor captación de ácidos grasos y una mayor hidrólisis de triglicéridos intrahepáticos (41). El EPA modula diferencialmente la adipogénesis y reduce el tamaño de la gota lipídica en los adipocitos, debido a que disminuye la expresión del PPAR-γ (42), y aumenta la expresión del gen de la enzima lipasa hormona sensible, lo que acelera la movilización de triglicéridos desde los adipocitos (42). Esto se traduce en una menor formación de adipocitos y en un menor contenido de grasa en ellos (42).…”
Section: Figuraunclassified